Learning Motivation as Mediating Variable on The Effect of Transformational Leadership on Job Performance - Kiswanto, Nanda; Yulianti, Praptini (Manunggal Halim Jaya, 2025)
This study examines and analyzes the effect of transformational leadership on learning motivation and job performance and the effect of learning motivation as a mediating variable. This research was conducted by distributing questionnaires to research respondents, namely employees in factory 1 grade 5, 6, and 7 (operator level) at PT. Petrokimia Gresik, Indonesia, with 207 employees as the respondents. Data were analyzed using Structural Equation Modeling (SEM) Partial Least Square (PLS). Findings: The results of this study state that transformational leadership has a significant positive effect on learning motivation and job performance. Learning motivation also has a significant positive effect on job performance. In addition. The existence of this research has implications that state that in increasing employee job performance, transformational leadership and learning motivation need to be improved. Learning motivation acts as a partial mediating variable in mediating the relationship between transformational leadership and job performance, which later becomes a new finding in this study.